IMPROVING STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT BY USING WALT DISNEY MOVIE TRAILER - Hutabarat, Nova Mawar; Tarigan, Natalia Widya Pasca (Bahasa Indonesia Prima, 2021)
ABSTRACT The purpose of this research was to find out the improvement of the students’ writing narrative text by using Walt Disney Movie Trailer and to investigate the process of writing narrative text by using Walt Disney Movie Trailer. The sample of this research took one class, the third grade of SMP Negeri 38 Medan by using applying Classroom Action Research is done in two Cycles. To collect the data, the researcher took Quantitative and Qualitative data. The quantitative data was collected by giving writing Essay test. The qualitative data was taken from observation sheet to investigate the situation and the problems found during the teaching and learning process and diary notes aimed to note personal evaluation about the situation of the class when teaching and learning process in each Cycles, and interview sheet to interview the English teacher and students before and after conducting the research. The result of the students’ mean score for Cycle I was 71,35 , and the students’ mean score for Cycle II was 85,6. It also could be seen from the percentage of the students who got score 75. In the Cycle I was 60% got the score 75 and the Cycle II was 100%. During the research in every meeting the students present in the class and the students write narrative text based on steps in writing. It can be concluded that Walt Disney Movie Trailer significantly improve the students’ writing narrative text. It is suggested that English teachers to apply Walt Disney Movie Trailer in teaching writing especially in writing narrative text. Key words: Writing Narrative Text, Walt Disney Movie Trailer.